Digitalisasi Dakwah: Tantangan dan Strategi Menginspirasi di Era Teknologi - Staniyah, Alfi Mardhiyatus; Efendi, Nur; Mashudi, Kojin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Digitalization has affected various aspects of human life, including the spread of religious teachings through da'wah. This research focuses on analyzing the impacts and challenges of digitalization in the context of da'wah, as well as strategies that can inspire more effective use of technology. The research method used is literature review, which relies on the search, selection, and critical evaluation of various primary data sources, such as scholarly journals, books, articles, and related scientific publications. The results of the data analysis led to findings that identified challenges in technology adoption in proselytizing, including a lack of technological knowledge, the risk of disseminating false or misleading information, as well as data integrity and information security. On the other hand, the research also outlined inspiring strategies, such as increasing dai capacity and competence to educational approaches and partnerships with government agencies to help overcome these challenges. The research aims to provide in-depth insights and a better understanding of technology integration in da'wah, strengthening the role of religious teachings in the modern technological era.